Global Research Trends on Occupational Health and Safety in Informal Sector Workers (2010-2025): A Bibliometric Study - Iksaruddin Iksaruddin; Onny Setiani; Sutopo Patria Jati; Yuliani Setyaningsih (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2026)
Introduction: Occupational health and safety (OHS) among informal sector workers is a growing global concern, as this workforce, representing approximately 60% of the world’s total employment, often operates outside formal regulatory and social protection systems. Informal workers face elevated risks of occupational injuries, hazardous exposures, and poor access to healthcare. This study analyzes global research trends on OHS in informal sector workers from 2010 to 2025 through a bibliometric approach. Methods: A bibliometric study was conducted using the PubMed database to identify relevant articles published between 2010 and 2025. The search yielded 235 eligible articles, which were analyzed using VOSviewer for keyword co-occurrence, thematic clustering, and collaboration network mapping. The PICO framework guided the analysis, focusing on research trends, hotspots, and collaborative patterns related to OHS in the informal sector. Results: The number of publications increased markedly after 2018, reaching a peak of 32 papers in 2021. Most studies originated from Asia (43%), followed by Africa (28%) and Latin America (17%). Keyword analysis revealed four dominant clusters: “occupational exposure” (47 occurrences), “workplace safety” (39), “precarious employment” (29), and “vulnerable workers” (22). International collaboration accounted for approximately 35% of total publications, showing a gradual upward trend in recent years. Conclusion: Global research on OHS in informal workers has grown substantially but remains quantitatively limited relative to the size of the informal workforce. Most studies emphasize hazard identification rather than preventive interventions. Greater cross-country collaboration and policy-oriented research are essential to strengthen OHS protection for informal sector workers worldwide.